2010
DOI: 10.1111/j.1741-6787.2009.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study to Test the Use of a Mobile Device in the Clinical Setting to Access Evidence-Based Practice Resources

Abstract: Students were able to complete the EBP activity using either the mobile device or PC and reported improvements in their knowledge and skills in relation to EBP and the appraisal of clinical guidelines. Findings suggest that for undergraduate health care students, rapid access to online evidence in the clinical environment is not necessarily essential for the integration of the EBP process into practice, or for the development of EBP knowledge and skills, provided there is easy access to such evidence at some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
(38 reference statements)
0
33
0
Order By: Relevance
“…There was no evidence of reliability testing for the questionnaires used in 17 studies. Scant evidence of face and content validity was provided in three studies [16,19,20]. Future investigative work on psychometric properties of a subjective and objective mobile technology metrics or measurement instrument would contribute to the development of a reliable and valid measurement to assess outcomes of mobile technology integrated into curricula of health professions education beyond the internal, local, or institutional application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no evidence of reliability testing for the questionnaires used in 17 studies. Scant evidence of face and content validity was provided in three studies [16,19,20]. Future investigative work on psychometric properties of a subjective and objective mobile technology metrics or measurement instrument would contribute to the development of a reliable and valid measurement to assess outcomes of mobile technology integrated into curricula of health professions education beyond the internal, local, or institutional application.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Morris and Maynard showed a low utilization of iPad at the clinical setting, primarily due to practical difficulties associated with accessing the Internet and small screen size on the device [20].…”
Section: Nursing Students' Use Of Mobile Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Morris and Maynard (2010) The 2009 Report (Johnson, Levine, & Smith, 2009) for the third year labels mobiles, primarily mobile phones, as a trend to watch. The opportunity for higher education to reach out and connect using mobile content is listed as a critical challenge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nursing and health care education were early adopters of using mobile technologies to connect students with information resources (Parsons, 2010 As Morris andMaynard (2010) highlight andLippincott (2010) emphasizes, in order to be truly mobile, devices need data plans. Kenny et al (2012) include discussion about who should be responsible for paying for data plans while Lippincott (2010) asserts that the provision of data plans is outside of the scope of library services.…”
Section: Literature Reviewmentioning
confidence: 99%